Biologic Use in Pediatric Patients With Hidradenitis Suppurativa: A Systematic Review. Issue 2 (March 2022) - Sachdeva, Muskaan; Kim, Patrick; Mufti, Asfandyar; Maliyar, Khalad; Sibbald, Cathryn; Alavi, Afsaneh
Background: There is currently at least 1 biologic (adalimumab) approved in North America for treatment of Hidradenitis Suppurativa in the pediatric population. However, no reviews or clinical trials have specifically analyzed the effectiveness and safety data of biologic use in this population. The objective of this systematic review is to identify and summarize the outcomes of biologic therapy in pediatric patients with HS. Methods: MEDLINE and EMBASE databases were used to conduct the search on Sept 18, 2020. Results: The 15 included studies consisted of 26 patients, with the mean age of 15 ± 2.3 years. Females accounted for 53.8% ( n = 14/26) of cases. The mean duration of HS prior to biologic initiation was 3.5 ± 2.9 years, with the majority having Hurley Stage II. The 26 patients received 34 biologics in total: 85.3% treated with TNF alpha inhibitors (adalimumab n = 17, infliximab n = 10, etanercept n = 1, unspecified n = 1), 5.9% with IL-12/23 inhibitors (ustekinumab n = 2), 5.9% with IL-1 inhibitors (i.e., anakinra n = 2) and 2.9% received IL-23 inhibitors (i.e., guselkumab n = 1) biologics. Of the 26 patients, 23.1% ( n = 6/26) experienced complete resolution (CR), 73.1% ( n = 19/26) experienced partial resolution (PR), and 3.8% ( n = 1/26) had no resolution outcomes reported. The time to resolution of HS lesions after biologic initiation ranged from 10 days to 11.5 months (mean: 5.1 months). No adverse events were reported in the studies. Conclusion: Although anti-TNF alpha were the most common biologics used for HS in pediatric cases, large-scale trials specific to pediatric patients with HS are needed to confirm these findings.